CARDIOVASCULAR SYSTEM, HEART, AORTA, EXTERNAL AND INTERNAL SLEEP ARTERIES, BLOOD SUPPLY TO THE SCALP - Saliyeva Minaraxon Yulbarsovna (University Research Base, 2024)
The cardiovascular system, comprised of the heart and network of arteries and veins, is the body's transportation system that delivers oxygen, nutrients, hormones, and cellular waste products throughout the body. At the center of this complex circulatory network lies the heart, which acts as a muscular pump to propel blood into the arteries. This article will examine key components of the cardiovascular system involved in supplying blood specifically to the scalp region of the head.